Digital ethnography: bibliometric analysis in Ibero-American communication field - Quintana-Pujalte, Leticia (2023)
The rise of the digital age has presented a significant challenge for social science research methods to adapt. Among the numerous theoretical and methodological approaches under discussion, this article examine the current situation of studies that use digital ethnography as an approach in Ibero-America. From a bibliometric method the objective is to analyze publications indexed in renowned global and regional databases, such as Scopus, Latindex and Web of Science. The purpose is to identify the approaches, influential figures and conceptual frameworks predominant in this area today. The results reveal that, despite its effectiveness in analyzing digital communities and relationships between users, digital ethnography needs to consolidate its epistemological foundations in the Ibero-American context. A marked use of theoretical contributions from outside the region is observed. However, it is encouraging to note that in Ibero-American studies that use digital ethnography, the prominent figures are women, which contributes positively to diversity and equity in scientific production in this area.